Z-plasty, an option for reconstructing two synchronous nasal defects: a case report - Raul Ribeiro Garcia; Luis Felipe Stella Santos; Guilherme Basso Durães; Lissa Shizue Tateiwa Niekawa; Rogerio Nabor Kondo (Surgical & Cosmetic Dermatology)
Z-plasty, a versatile surgical technique, skillfully addresses diverse needs in dermatological surgeries, especially the lengthening, dispersion, and realignment of scars through relaxed skin tension. We report a case of two synchronous defects after excising nasal squamous cell carcinomas using the Z-plasty technique, highlighting its simplicity, adaptability and esthetics.